APUNTES SOBRE EL TRATAMIENTO JURÍDICO DEL SILENCIO EN EL DERECHO ADMINISTRATIVO Y EN EL DERECHO TRIBUTARIO - Rodríguez Vargas, Luis Felipe (2021)
The present article focuses on the study of the legal treatment of silence. Placing its background in Roman and Canon Law, it is possible to understand how its nature and purpose end up being shaped in Administrative Law. Once its main characteristics have been addressed, this work proceeds to determine how this concept operates in Tax Law, in which it has very specific particularities.